The Phenomenon Of Dating Behavior Of Teenagers Living Separate From Their Parents Among Sumba Students In Kediri; Qualitative Study - Sejati, Putri Eka; Irawati Benge; Eri Puji Kumalasari; Devy Putri Nursanti (Universitas STRADA Indonesia, 2024)
Teenagers are in a transition period from asexual to sexual, One of the functions of the family is to control teenage behaviour.This research used qualitative study. The informants in this research were four Sumba students aged 19-24 who lived separately from their parents. The results obtained were that 3 of the informants had held hands, hugged, and kissed but had never had sexual intercourse or consumed alcohol. In contrast, one informant had sexual intercourse under the influence of alcohol and without using a condom; the four informants said their parents never controlled their sexual behaviour. Based on the research results, it can be concluded that two teenagers were dating in a crowded place and never engaged in risky sexual activities because they were afraid of their parents. In contrast, teenagers who had engaged in risky sexual activities and had sex said their parents would not know about their behaviour.